Voz do cantor lírico: efeitos da aplicação de um programa de desenvolvimento da coordenação motora baseado em Piret e Béziers - Mello, Enio Lopes (2008)
The motor coordination is the ability for organizing the movement in time and space. This organization is the result of integration between brain command and muscles and articulations motor units. So the motor answers happen in muscle chains where a stimulus sets in motion a muscle and this in his turn sets in motion another muscle, and so on and so forth. We started from the notion that the singing voice is not the result of one organ but it is the result of a group of structures that coordinate themselves. Objective: to investigate the effect of the application of a Motor Coordination Development Program (MCDP), elaborated by the researcher, based on Piret and Béziers, in the voice of the lyric singer. Method: this research counted on the participation of five professional lyric singers. The singers executed an aria of opera of free choice that was filmed pre and post intervention. They also answered on the proprioception when singing as well as pre and post MCDP exercises. During one month they were submitted to the MCDP that mainly worked on the structure of the straight system and crossed system. The videos were sent to nine professional judges (speech therapist, physical therapist and singing teachers) and three laypeople. The Judges made audio perception and visual analysis to evaluate the body / voice integration of the singers. The singers made auto-evaluation right after attending the two filmings. Result: judge s evaluation: the mezzo-soprano improved the projection of the voice and corporal gestures were free; the bass improved the projection of the voice and breath; the soprano (b) improved the projection of the voice and the gestures were freer; the tenor improved the resonance and the gestures were freer; soprano (a) improved the projection of the voice and the gestures were freer. According to the singers report, the MCDP exercises guaranteed greater perception of the muscular tension when singing and it made possible a better control of gestures. Conclusions: the postural adjustments deriving from the execution of the motor coordination exercises guaranteed greater opening of the thoracic cavity and improved the conditions of the singers breath. This favored the verticalization of the resonance and projection of the voice